Proton long-range migration along protein monolayers and its consequences on membrane coupling - Gabriel, B. (The National Academy of Sciences of the USA, 1996)
It has been shown with lipid layers and more recently with purple membranes that protons have slow surface-to-bulk transfer. This results in long-range proton lateral conduction along membranes. We report here that such lateral transfer can take place along a pure protein film. It is strongly controlled by the packing. Subtle reorganizations of the protein–protein contact can be biological switches between interfacial and delocalized proton pathways between sources and sinks.